Bioactive glasses ; Materials, properties and applications - Ylanen, Heimo O.; ScienceDirect eBooks (Cambridge : Woodhead Publishing Ltd, 2011)
Due to their biocompatibility and bioactivity, bioactive glasses are used extensively as implant materials throughout the human body to replace or repair damaged tissue. This title provides the reader with a comprehensive review of the status of this material and its applications, technologies and future trends. Due to their biocompatibility and bioactivity, bioactive glasses are used as highly effective implant materials throughout the human body to replace or repair damaged tissue. As a result, they have been in continuous use since shortly after their invention in the late 1960s and are the subject of extensive research worldwide. Bioactive glasses provides readers with a detailed review of the current status of this unique material, its properties, technologies and applications. Chapters in part one deal with the materials and mechanical properties of bioactive glass, examining topics such as surface modification and cell interaction. Part two is focussed on.
Part 1 Materials and mechanical properties of bioactive glass: Melt-derived bioactive glasses -- Surface modification of bioactive glasses -- Cell interaction with bioactive glasses and ceramics -- Regulatory aspects of bioactive glass. Part 2 Applications of bioactive glass: Bioactive glass and glass ceramic scaffolds for bone tissue engineering -- Nanoscaled bioactive glass particles and nanofibres -- Bioactive glasses containing composites for bone and musculoskeletal tissue engineering scaffolds -- Use of bioactive glasses as bone substitutes in orthopaedics and traumatology -- Bioactive glass S53P4 as a bone graft substitute in the treatment of osteomyelitis -- Bioactive glass for maxillofacial and dental repair -- Bioactive glass and biodegradable polymer composites -- Bioactive glasses for wound healing.
Heimo O. Ylanen is Professor of biomaterials science at Tampere University of Technology, Finland.
Elsevier
Keywords: Biomedical materials; Glass-ceramics.; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Biomedical materials; Glass-ceramics.; Bioaktive Verbindungen; Glas; Bioaktive Verbindungen; Glas; Electronic books